3차원 입체조형치료에 의한 아교모세포종의 방사선 선량증가 연구 - 조재호(Jae Ho Cho), 이창걸 김경주(Kyoung Ju Kim)(Chang Geol Lee), 박진호(Jino Bak), 이세병(Se Byeoung Lee), 조삼주(Sam Ju Cho), 심수정(Su Jung Shim), 윤덕현(Dok Hyun Yoon), 장종희(Jong Hee Chang), 김태곤(Tae Gon Kim), 김동석(Dong Suk Kim), 서장옥(Chang Ok Suh) (Radiation oncology journal, 2004)
KCI Citation Count: 1